The sciopticon manual : explaining Marcy's new magic lantern and light, including magic lantern optics, experiments, photographing and coloring slides, etc. / by L.J. Marcy. - Marcy, L. J. (Tufts University. Tisch Library., 2015)
Revised edition.; xii, 124, 55 pages : illustrations ; 20 cm.; "The sciopticon and dissolving view apparatus with a priced catalogue of magic lantern slides. Revised edition" : 55 pages at end.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.